PENERAPAN STRATEGI STP (SEGMENTING, TARGETING, POSITIONING) - Sujianto Sujianto (Prodi Teknik Industri S1 Institut Teknologi Nasional Malang, 2011)
PT. Cool Clean represent one of the factory which producing wet tissue which located in Unlucky region, in running its out for to effort always improve sale along with more and more competitor him offering product of a kind resulting degradation of sale volume.To be able to improve sale hence needing the existence of research that PT. Cool Clean have constraints faced, to increase sale volume by propagating kuesioner. So that for tight facing of emulation him in this effort, hence needed of the research by using strategy of STP (Segmenting, Targeting, Positioning) utilize tight facing of the emulation.The method wich used is strategy of STP (Segmenting, Targeting, Positioning) by using program of SPSS Version 12.00 For Windows in analysis of Cluster for selected by Segmenting is the first segment that is: old fellow circle, wiraswasta, owning production of Rp. 1.001.000,00 to Rp. 1.500.000,00, usefull, the midle of enough using, using by the time of weeding party, and give positive comments to the product. At the analysis of the Targeting which used by method analyse market compartment one of them market segment. Result of Positioning with method of Image Analysis Model got by product position pursuant to target market that is: quality of product enough with quality, desain enough draw, cheap product price, and usefulness enough good for.